Pemberdayaan Pasien dan Keluarga dengan Home Visit Serta Support Group Dalam Pengendalian Stroke pada Lansia di Rumah - Vivi Yuderna; Mike Asmaria; Hilma Yessi; Hasmita Hasmita; Sandra Dewi (Jurnal Medika: Medika, 2025)
Factors such as gender, age, education, history of high blood pressure, cholesterol levels, excess weight, coronary heart disease, smoking, high salt consumption, and lack of physical activity can increase the risk of stroke. The La-Tulip Integrated Health Service Post (Posyandu) in Pauh Barat village generally has these factors, particularly hypertension, diabetes, elderly, and hereditary factors. Therefore, mitigation efforts are needed through home visits and support groups. The goal of community service is to empower patients and their families to participate alongside the elderly in controlling stroke risk factors, especially in patients with diabetes mellitus and hypertension. The community service methods include health education, home visits and support groups, evaluation, and monitoring. The number of participants was 5 stroke patients and 5 high-risk patients, along with 9 family members or caregivers. The evaluation results showed an increase in knowledge, skills, and behavioral management of stroke prevention and patient care among the majority of patients and their families. Patients and families were better guided and monitored, enabling them to maximize their care. After the home visits and support groups, it is hoped that families will be able to implement the education provided optimally.